(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
The Punjab State Co-operative agricultural and rural development bank is playing an important role in meeting long-term credit requirement of rural population in the state. In this paper an attempt has been made to estimate the impact of selected variables on ADBs’ advances for the period of 1999-00 to 2012-13. The underlying objective is to test empirically the selected variables, which have significantly contributed towards ABDs’ loans in either direction at 1% and 5% percent level of significance. It is done in two sections, firstly for Punjab State Cooperative Agricultural Development Bank and secondly for its member banks i.e. Primary Cooperative Agricultural Development Banks on the basis of selected variables.. In PSCADB the loans and advances and all other varibles are not correlated with profits. The matrix indicates that all varibles are positively correlated with each other except number of employees. The regression coefficient explains that one unit increase in owned funds will increase the loans and advances. In PADBs, the matrix indicats that all varibles are positively correlated with each other except number of employees. Membership is not correlated with loans and advances. The regression coefficient explains that one unit increase in borrowings will increase the loans and advances.